DESAIN DAN PERANCANGAN SISTEM INFORMASI BERBASIS KOMPUTER DALAM PENGOLAHAN DATA BEROBAT PADA BALAI PENGOBATAN UMMAT PASIR PENGARAIAN DENGAN MENGGUNAKAN BAHASA PEMOGRAMAN VISUAL BASIC 6.0 - Yasdomi, Kiki (E-Journal Cano Ekonomos, 2013)
Clinical Centre of Ummat Pasir Pengaraian is an peripatetic place in the field of place or medication medicinize to society. At clinical centre of ummat in data processing medicinize still manually, therefore better exploit information technology which continue to expand in this time, in expection of its data processing more precise and is efficient. As for research method the used is research of field, research of library and research of laboratory. So that in yielding a new system analysis by using appliance assist like ASI (Stream Information System), DFD (Data of Flow Diagram), ERD (Entity Relationship Diagram), and Context Diagram. By means of assist this is later will be yielded by some file which each other interconnected in a database management. Database management very needed in scheme of new system to facilitate to access to each;every file in it. Database to be yielded to consist of 4 (file fruit empat), that is patient file, medication file, file medicinize and receipt file.